Bahasa Indonesia vs Bahasa Jerman: Perbedaan Tata Bahasa yang Perlu Diketahui - Michela Michela; Shayka Annisa Idris; Tresia Simangunsong; Rosmayani Tambunan; Nurul Azzizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Indonesian and German originate from different language families, namely Austronesian and Germanic. This distinction leads to significant grammatical differences between the two languages. This article explores key aspects that differentiate Indonesian and German grammar, including sentence structure, case system, verb conjugation, article usage, and compound word formation. Understanding these differences helps language learners avoid common mistakes and enhance their proficiency in both languages. This study is supported by various sources from recent books and academic articles to provide a more comprehensive analysis.